25 years of advances in the definition, classification and treatment of status epilepticus. (January 2017) - Trinka, Eugen; Kälviäinen, Reetta
Highlights: Morbidity and mortality of SE correlate with duration of status, the rapid identification of the cause of SE, age and comorbidity. Treatment should be started when a seizure is abnormally prolonged (time-point t1). Time point t1 for generalized tonic clonic seizures is at 5 min, and for focal seizures at 10 min. At time-point t2 neuronal damage may begin, and indicates that SE should be controlled latest by that time. A staged protocol with early, established, refractory and super-refractory stages is the hallmark of current SE treatment. Abstract: Purpose: Status epilepticus (SE) requires not only urgent symptomatic treatment with antiepileptic drugs but also rapid identification and treatment of its cause. This narrative review summarizes the most important advances in classification and treatment of SE. Method: Data sources included MEDLINE, EMBASE, ClinicalTrials.gov, and back tracking of references in pertinent studies, reviews, and books. Results: SE is now defined as "a condition resulting either from the failure of the mechanisms responsible for seizure termination or from the initiation of mechanisms, which lead to abnormally, prolonged seizures (after time point t1). It is a condition, which can have long-term consequences (after time point t2), including neuronal death, neuronal injury, and alteration of neuronal networks, depending on the type and duration of seizures." A new diagnostic classification system of SE introduces four axes: semiology, aetiology, EEG correlates, and age. For the acute treatment intravenous benzodiazepines (lorazepam, diazepam, clonazepam) and intramuscular midazolam appear as most effective treatments for early SE. In children, buccal or intranasal midazolam are useful alternatives. In established SE intravenous antiepileptic drugs (phenytoin, valproate, levetiracetam, phenobarbital, and lacosamide) are in use. Treatment options in refractory SE are intravenous anaesthetics; ketamine, magnesium, steroids and other drugs have been used in super-refractory SE with variable outcomes. Conclusion: Over the past 25 years major advances in definition, classification and understanding of its mechanisms have been achieved. Despite this up to 40% of patients in early status cannot be controlled with first line drugs. The treatment of super-refractory status is still an almost evidence free zone.